(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
This article considers the subsidization of railway transport organizations in terms of lost income from the transportation of preferential categories of citizens. Preferential categories of citizens are defined. Positive and negative aspects of subsidies have been identified.